+0  
 
0
293
3
avatar+2353 

Define the system of equations;

$$x_{n+1} = x_n - y_n$$

$$y_{n+1} = 2x_n + 4y_n$$

so if we take $$A = \begin{pmatrix}
1 & -1\\
2 & 4
\end{pmatrix}$$

and define

$$\begin{pmatrix}
x_{n+1} \\
y_{n+1} \\
\end{pmatrix} = \begin{pmatrix}
1 & -1 \\
2 & 4 \\
\end{pmatrix}\begin{pmatrix}
x_n \\
y_n \\
\end{pmatrix}$$

Then given that the eigenvalues and a corresponding eigenvector to the eigenvalue can be defined as

$$\lambda_1 = 3$$

$$\mu_1 = \begin{pmatrix}
1 \\
-2 \\
\end{pmatrix}$$

$$\lambda_2 = 2$$

$$\mu_2 = \begin{pmatrix}
1 \\
-1
\end{pmatrix}$$

(I already checked this)

Is it then true that the general solution can be defined as

$$x_n = 3^nc_1 + 2^nc_2$$

$$y_n = -2*3^nc_1 - 2^nc_2$$

Reinout 

reinout-g  Jun 2, 2014

Best Answer 

 #3
avatar+889 
+5

Hi Reinout

Yes, agree with your result, with

c1 = -x0 - y0  and  c2 = 2x0 + y0 .

Bertie  Jun 2, 2014
Sort: 

3+0 Answers

 #1
avatar+26402 
+5

Perhaps I've misunderstood, but if c1 and c2 are initial values (n=0) for x and y then (for n = 1):

reinout

These don't look the same to me!

Alan  Jun 2, 2014
 #2
avatar+2353 
+5

Hey Alan,

you're right, but they are not initial values.

They are constants which can be calculated for given initial values for x and y

reinout-g  Jun 2, 2014
 #3
avatar+889 
+5
Best Answer

Hi Reinout

Yes, agree with your result, with

c1 = -x0 - y0  and  c2 = 2x0 + y0 .

Bertie  Jun 2, 2014

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details